ANALISIS SIKAP KONSUMEN TERHADAP BRAND CLOTHING LOKAL LOMBOK (Study Pada Konsumen Di Wilayah Kota Mataram) - Masyhur Kusudyadmoko; Lalu Adi Permadi; Baiq Handayani Rinuastuti (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2019)
This study aims to analyze the influence to find out and analyze consumer attitudes towards Lombok's local clothing brand. This type of research is descriptive quantitative. The population in this study was consumers of the local Lombok clothing brand in the city of Mataram. The number of samples is 100 people. Data collection techniques were conducted using questionnaires, documentation, and interviews, while the data collection tools used questionnaires. The analytical tool used is Fishbein Attitude Model. The results of the study indicate that: The response or attitude of consumers in the city of Mataram to the attributes of design, brand, quality, and model of Lombok's local clothing brand is very good or positive. After analyzing consumer attitudes towards Lombok's local clothing brand, the respondents considered the first thing to be considered when making a purchase of a local Lombok clothing brand product is Design, then the next assessment is Brand, Kualita, and the last is the Model of the product own. When consumers evaluate after making a purchase, the Brand, Quality and Model attributes experience a positive increase. However, the Design attribute experienced a slight decrease after consumers conducted an evaluation, this shows that although Design attributes have the highest value among other attributes, they still experience a slight decrease after consumers evaluate product purchases.